Movement-related dynamics of cortical oscillations in Parkinson’s disease and essential tremor - Kondylis, Efstathios D.; Randazzo, Michael J.; Alhourani, Ahmad; Lipski, Witold J.; Wozny, Thomas A.; Pandya, Yash; Ghuman, Avniel S.; Turner, Robert S.; Crammond, Donald J.; Richardson, R. Mark (Brain (London, England : 1878), 2016)
Recent electrocorticography data have demonstrated excessive coupling of beta-phase to gamma-amplitude in primary motor cortex and that deep brain stimulation facilitates motor improvement by decreasing baseline phase-amplitude coupling. However, both the dynamic modulation of phase-amplitude coupling during movement and the general cortical neurophysiology of other movement disorders, such as essential tremor, are relatively unexplored. To clarify the relationship of these interactions in cortical oscillatory activity to movement and disease state, we recorded local field potentials from hand sensorimotor cortex using subdural electrocorticography during a visually cued, incentivized handgrip task in subjects with Parkinson's disease (n = 11), with essential tremor (n = 9) and without a movement disorder (n = 6). We demonstrate that abnormal coupling of the phase of low frequency oscillations to the amplitude of gamma oscillations is not specific to Parkinson's disease, but also occurs in essential tremor, most prominently for the coupling of alpha to gamma oscillations. Movement kinematics were not significantly different between these groups, allowing us to show for the first time that robust alpha and beta desynchronization is a shared feature of sensorimotor cortical activity in Parkinson's disease and essential tremor, with the greatest high-beta desynchronization occurring in Parkinson's disease and the greatest alpha desynchronization occurring in essential tremor. We also show that the spatial extent of cortical phase-amplitude decoupling during movement is much greater in subjects with Parkinson's disease and essential tremor than in subjects without a movement disorder. These findings suggest that subjects with Parkinson's disease and essential tremor can produce movements that are kinematically similar to those of subjects without a movement disorder by reducing excess sensorimotor cortical phase-amplitude coupling that is characteristic of these diseases.